Phase transition in BaThO3 from Pbnm to Ibmm turn the fundamental energy band gap from indirect to direct - Reshak, Ali Hussain; Alahmed, Zeyad A.; Bila, Jiri (Elsevier, 2019)
The influence of phase transition on the electronic structure and the optical properties of BaThO3 is investigated by means of density functional theory. At room temperature BaThO3 is stable in the Pbnm phase, whereas it is stable in the Ibmm phase at high temperature. The transition from the Pbnm to the Ibmm phase cause a change in the band gap (Eg) nature from indirect to direct and a reduction by around 0.3 eV. The calculated Eg is about 4.9 eV (Pbnm) and 4.6 eV (Ibmm). The phase transition influences the k-dispersion of bands around the Fermi level and, hence, the effective masses resulting in increasing the mobility of the charge carrier and enhancing the charge transfer mechanism. The obtained optical properties clearly show the influence of phase transition on the electronic structure. It was noticed that moving from Pbnm →Ibmm phase leads to shift the whole spectral structure towards lower energies by around 0.3 eV and increase the magnitudes of the optical components. It is found that the Pbnm and Ibmm phases exhibit negative uniaxial anisotropy and negative birefringence.